Reconsidering the Alleged Cases of Knowledge from Falsehood*. (10th November 2020) - Lee, Kok Yong
Abstract: A number of philosophers have recently proposed several alleged cases of "knowledge from falsehood, " i.e., cases of inferential knowledge epistemised by an inference with a false crucial premise. This paper examines such cases and argues against interpreting them as cases of knowledge from falsehood. Specifically, I argue that the inferences in play in such cases are in no position to epistemise their conclusions.